2010
DOI: 10.1128/aem.02127-09
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Pathogens and Indicator Microbes at a Non-Point Source Subtropical Recreational Marine Beach

Abstract: Swimming in ocean water, including ocean water at beaches not impacted by known point sources of pollution, is an increasing health concern. This study was an initial evaluation of the presence of indicator microbes and pathogens and the association among the indicator microbes, pathogens, and environmental conditions at a subtropical, recreational marine beach in south Florida impacted by non-point sources of pollution. Twelve water and eight sand samples were collected during four sampling events at high or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
143
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(154 citation statements)
references
References 47 publications
6
143
1
1
Order By: Relevance
“…Future work will need to integrate molecular surveys of airborne communities with atmospheric chemical transport models across more extensive sample sets in order to more confidently determine bacterial sources and map their atmospheric trajectories over extended time periods. However, just as we can use bacterial taxa indicative of animal feces to track fecal contamination of bodies of water (Brownell et al, 2007;Abdelzaher et al, 2010;Wery et al, 2010) or use bacterial communities on the hands of different individuals to identify touched objects , we may be able to use bacterial taxa indicative of possible source environments to identify and compare inputs of bacteria with the atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Future work will need to integrate molecular surveys of airborne communities with atmospheric chemical transport models across more extensive sample sets in order to more confidently determine bacterial sources and map their atmospheric trajectories over extended time periods. However, just as we can use bacterial taxa indicative of animal feces to track fecal contamination of bodies of water (Brownell et al, 2007;Abdelzaher et al, 2010;Wery et al, 2010) or use bacterial communities on the hands of different individuals to identify touched objects , we may be able to use bacterial taxa indicative of possible source environments to identify and compare inputs of bacteria with the atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that beach sand may serve as a reservoir for pathogens harmful to human health and indicator microbes that can be released into surrounding waters through tidal action or run-off (Alm et al, 2003;Whitman and Nevers, 2003;Boehm and Weisberg, 2005;Beversdorf et al, 2007;Colford et al, 2007;Fleisher et al, 2010;Ge et al, 2010;Sinigalliano et al, 2010;Abdelzaher et al, 2010). Several authors have reported that both indicator bacteria and potential pathogens occur in beach sands of both freshwater and marine environments (Sanchez et al, 1986;Ghinsberg et al, 1994Ghinsberg et al, , 1995Obiri-Danso and Jones, 2000;Desmarais et al, 2002;Sato et al, 2005;Vantarakis et al, 2005;Beversdorf et al, 2007;Bonilla et al, 2007;Vogel et al, 2007;Hartz et al, 2008;Abdelzaher et al, 2010).…”
Section: Bacteriamentioning
confidence: 99%
“…Pinto et al (2012) found elevated levels of fecal indicators and parasites in the sand of beaches from São Paulo, Brazil. Abdelzaher et al (2010) found that enterococci in sand beaches of a south Florida, USA beach correlated with supplemental FIB (fecal coliforms, E. coli, and Clostridium perfringens) in both water and sand samples. Pathogens were detected predominantly during the same sampling event that resulted in the highest indicator microbe levels.…”
Section: Microbiological Agents Found In Sands Of Bathing Areasmentioning
confidence: 99%
See 2 more Smart Citations